1955
DOI: 10.1139/m55-090
|View full text |Cite
|
Sign up to set email alerts
|

THE ACTION OF T2 BACTERIOPHAGE GHOSTS ON ESCHERICHIA COLI B

Abstract: A study of the physiological effects of T2 ghosts, prepared by the method of Anderson, has been made. It was found that 75% of the ghosts can be adsorbed to host cells as measured with S35. Of these, only 10 to 35% are killers. The remainder, although adsorbed, do not prevent colony formation. A number of experiments, both in liquid culture and on agar plates, show that the effect of this latter class of particles is a temporary one. They lead to an arrest in bacterial multiplication, to a very marked inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1959
1959
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 6 publications
2
43
0
Order By: Relevance
“…1). Since ghosts have been reported to be adsorbed at the same rate as phage (3,12), this cannot be explained by a difference in adsorption. The effect of ghosts on cells in which the TMG concentration has reached a steady state is shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1). Since ghosts have been reported to be adsorbed at the same rate as phage (3,12), this cannot be explained by a difference in adsorption. The effect of ghosts on cells in which the TMG concentration has reached a steady state is shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Infection of Escherichia coli by T4 bacteriophage results in inhibition of cellular macromolecular syntheses, multiplication of the phage, and eventual lysis of the cell (4). The addition of the deoxyribonucleic acid (DNA)-less protein coat of the phage, a phage ghost, to E. coil also will inhibit and subsequently kill the host bacterium, although the phage ghost cannot, of course, multiply (12,15). In this respect, the action of ghosts seems analogous to the effects of some colicins (18).…”
mentioning
confidence: 99%
“…They found that P-galactosidase was not formed by these cells following the addition of the inducer, lactose. French & Siminovitch (1955) also found that this enzyme was not formed following infection with phage ghosts. Sher & Mallette (1954) also were unable to demonstrate the continued formation of the inducible lysine decarboxylase after addition of either phage T2r+ or phage ghosts.…”
Section: Introductionmentioning
confidence: 89%
“…Whether analogies should be sought between the effect of the T phages and of A phage on the metabolism of E. coli is, however, doubtful, since there appears to be a t least one fundamental difference between these two types of virus. The phage coats of the T viruses can themselves kill cells (Herriott, 1951;French & Siminovitch, 1955), whereas such a lethal effect has not been demonstrated with phage coats of either wild type or virulent mutants of h (Weigle, quoted by Bertani, 1958).…”
Section: B a Fry And F Grosmentioning
confidence: 99%